2021
DOI: 10.1108/prt-05-2020-0049
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterisation of multifunctional composite coatings using bio-based additives

Abstract: Purpose The purpose of this paper is to develop the bio-composite organic coatings by adding the bio-based additives that are extracted from banana peels and henna leaves as the organic corrosion inhibitors. Design/methodology/approach Bioactive constituents with inhibition properties are extracted from banana peels and henna leaves by using ethanol to form the ethanolic extract. The inhibiting efficiency of these bioactive constituents on mild steel corrosion in 3.5% sodium hydroxide (NaCl) solution is inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, there is no peak of 2,273 cm À1 which represents the N = C = O band disappeared in the AHPN spectrum . It can be confirmed that the coating had fully cured and the wellcrosslinking between acrylic resin and the polyisocyanate (NCO) curing agent (Ong et al, 2021).…”
Section: Fourier Transform Infraredmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, there is no peak of 2,273 cm À1 which represents the N = C = O band disappeared in the AHPN spectrum . It can be confirmed that the coating had fully cured and the wellcrosslinking between acrylic resin and the polyisocyanate (NCO) curing agent (Ong et al, 2021).…”
Section: Fourier Transform Infraredmentioning
confidence: 88%
“…Corrosion is the degradation of the material due to chemical reactions with environmental matters which acted as corrosive agents toward a metal surface (Ong et al , 2021). It is a natural process that cannot be avoided for most metal because by nature, the metal will intend to return to its natural state which is oxide form.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical impedance method was used to evaluate the corrosion performance. As a result, they revealed that banana peels and henna leaves can be used as anti-corrosion biocomposites (Ong et al , 2022).…”
Section: Introductionmentioning
confidence: 99%